Desenhos de couro: registro e memória dos desenhos no encouramento do vaqueiro sertanejo - Neiva, Suria Seixas (2017)
This dissertation presents the designs made from leather used by the brazilian northeast’s country cowboys: a type of surface design which can become a working gear but also a fashionable apparel. This tooled and carved leather has been made by generations in the sertão and it is named here after “desenho de couro”. The purpose of this work is to approach the manifestations of such ornamental leather technics considering their regional and historical presented aspects, or preexistences of its present form. The aesthetic and technical connections among the different expressions of the leather designs are understood through the survival dialetics of the images in the collective memory. This comes to be the art history methodology proposed by Warburg. Considering that is still possible to contact living masters of leather in activity, and to collect information regarding the technique transmission, this resource was used in order to understand the aesthetics and uses of that leather culture, which has its ancestral in the iberic-mudeyyan leatherwork. Both the documents of leather trade in the century XVIII, as well as of the history of the livestock in the Brazilian countryside corroborates with the hypotheses regarding the influence of the Iberian leather culture and its productive main points, today, in the Bahia countryside around Feira de Santana and Ipirá, as in Cariri from Pernambuco. The study of this leather design, more than a record of a Brazilian visual production, it is an living document of the national leather traditions and an outstanding element in the construction of the cowboy's identity as well as of an economic production and material culture of Brazil.